A atenção primária a saúde (APS) nos governos Temer e Bolsonaro (2016-2021): um olhar para a estratégia saúde da família (ESF) - Machado, Kyara Batista (Universidade Federal do Tocantins, 2022)
Since the beginning of the 1980s, social movements and other organizations of the subaltern classes launched themselves in the struggle for the redemocratization of society and the State, making this decade a milestone for Brazilian democracy. This time also marked an important moment for health policy, which gained the status of Social Security policy, strengthened within the scope of the citizen's right and the State's duty with the promulgation of the Federal Constitution of 1988. In the following years, with the advent of neoliberalism and its attacks on the rights of the working class, the Primary Health Care (PHC) policy has been suffering strong threats with the successive attempts of its privatization and with the limitation of its budget investment, since EC no. 95. Thus, in this study, we seek to understand how the primary care policy has been shaped in Brazil in the Temer and Bolsonaro governments during the period from 2016 to 2021. In order to approach the object of study, we used bibliographical research with an approach based on from the historical and dialectical materialism, which allowed us a theoretical framework and as a data collection technique, documental research was used. The survey results show that neoliberal attacks intensified during Michel Temer's government with the approval of EC 95/2016 and the PNAB counter-reform and gained strength during the government of Jair Messias Bolsonaro with the health policy subordinated to the market through privatizations and with the Prevent Brazil program.